Financial and Non-Financial Information Seeking: The Role of Managing Anger and Fear in Investment Strategies and Decision-making - Vahid Oskou; Sahar Yousefizadeh; Fatemeh Asnad (تحقیقات مالی)
ObjectiveIn Iran's capital market, investors get the information they need to make decisions from various sources. Affected by different emotions, decision-making is considered one of the most complex psychological issues. Investors' excitement influences how they behave and make decisions. Their emotional behavior may cause the capital market to undergo irrational processes. This study aims to examine the relationship between investors' excitement and their information search behaviors, with the ability to manage emotions serving as a moderating variable. MethodsFrom an applied research perspective, the results can be valuable for both researchers and investors. Methodologically, the study is descriptive and follows a deductive-inductive research logic. In terms of its temporal scope, it can be classified as cross-sectional research. This research is quantitative and employs a scenario-writing method. The data was collected using standard questionnaires. Data analysis was conducted using structural equation modeling and the software programs SPSS and Smart PLS. The statistical population in this research consists of all the investors who are active in the country in 2022. The sampling method was purposeful and non-probability, with participants selected from among available investors. The scenario execution method involved the following steps: In the first stage, participants were asked to make investment decisions between two different companies. After being presented with the investment options, participants received information about each company. This information included a description of the company's operations, a summary of the previous year's financial performance, financial data for the first and second quarters of the current year, and analysts' consensus forecasts for the company's earnings per share for the upcoming quarter and the current year. ResultsThe research findings reveal that the emotion of fear has a positive and significant effect on investors' behavior during information searches. Conversely, anger has a negative and significant impact on this behavior. Additionally, the results show that emotion management does not significantly moderate the relationship between fear and investors' information-seeking behavior. However, emotion management does have a positive and significant moderating effect on the relationship between anger and investors' information-seeking behavior. ConclusionIt can be concluded that both fear and anger significantly influence investors' information-seeking behavior. When investors are fearful about a decision and its outcome, they seek additional information to boost their confidence. This often leads to more conservative decision-making. Conversely, investors experiencing anger are less inclined to seek new information or process the information they have and are more likely to make hasty decisions.